Determination of candidal vulvovaginitis prevalence in patients referred to the gynecology clinic of Imam Khomeini Hospital, Noor City, Iran: Candidal vulvovaginitis prevalence in patients - Shaygan, Fatemeh; Zaboli, Fatemeh; Izadi-Amoli, Rabee (Chronic Diseases Journal, 2025)
BACKGROUND: Candidal vulvovaginitis is an infection of the female genital tract that is caused by overgrowth of Candida, especially Candida albicans (C. albicans), and it may sometimes be recurrent. This research aimed to determine Candidal vulvovaginitis prevalence in women by phenotypic tests and polymerase chain reaction (PCR). METHODS: This descriptive cross-sectional study was performed in Noor City, Iran, in 2017, on 36 patients with Candidal vulvovaginitis. Samples were isolated and identified by direct and phenotypic tests. Then, to confirm the isolates, molecular PCR and sequencing were used. Frequency determination was performed for them using SPSS software. RESULTS: Out of 15 isolates, 10 (66.67%) belonged to the C. albicans species and 5 (33.33%) isolates belonged to Candida glabrata (C. glabrata). PCR-sequencing showed that out of 15 isolates, 10 isolates were positive for C. albicans, and all 5 isolates were C. glabrata. CONCLUSION: C. albicans and C. glabrata species were the most common cause of Candidal vulvovaginitis. Although C. albicans is still the predominant species in patients with Candidal vulvovaginitis, the increase in non-albicans species is a fact that requires further research by researchers in this field.